Sustainable integrated farming system model for small farm holders of Uttar Pradesh - MEENA, L R; KOCHEWAD, S A; PRUSTY, A K; BHANU, CHANDRA; KUMAR, SANJEEV; MEENA, A L; MEENA, LALIT KRISHAN; RAGHAVENDRA, K J; KUMAR, DEVENDRA; SUBASH, N; Singh, S P (The Indian Journal of Agricultural Sciences, 2022)
The developed IFS model is having different components which comprise of arable crops (1.04 ha), horticulture crops (0.22 ha), fishery (0.10 ha), mushroom (0.02 ha), poultry (10 birds), vermicompost (0.02 ha) and kitchen garden (20 m2). The overall productivity of model was 174.04 tonnes/ha/year in terms of sugarcane equivalent yield (SEY) during the representative years (2013–18). The farmyard manure (FYM) together with vermicompost and other farm-based by-products saved the nutrients by 338.71 kg N, 124.60 kg P, 306.22 kg K and 769.56 kg NPK (kg/year). The entire annual man-days generated were 441, 465, 473, 467 and 470 in various components during 2013–14, 2014–15, 2015–16, 2016–17 and 2017–18, respectively. However, maximum man-days were generated by crop component (209/year) followed by dairy component (152/year) of the IFS model. The gross return/year/ha obtained was `6.12×103/ha and net returns of (`3.74×103/ha) with per day income of `1025 from 1.5 ha of the IFS model under irrigated agro-ecosystem. Inclusion of horticulture components and boundary plantations in the IFS model also tend to reduce GHG emissions.